2023
DOI: 10.1021/acs.jchemed.2c00868
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Model Teaching in the Postepidemic Period: From Nucleic Acid to Antigen for the Fluorescence Analysis of SARS-CoV-2

Abstract: Owing to the global spread of the coronavirus disease 2019 (COVID-19), education has shifted to distance online learning, whereas some face-to-face courses have been resumed with the improvement of the outbreak prevention and management situation, including a laboratory course for senior undergraduate students in chemical biology. Here, we present an innovative chemical biology experiment covering COVID-19 topics, which was created for third-year undergraduates. The basic principles of two nucleic-acid- and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…During that period, it was advised to regularly solicit feedback through low-stakes assignments to assess student learning and improve their courses while they were online . Feedback from students and the utilization of the recorded videos suggested that creating such content was not only valuable at that moment but also for future remote or in-person courses. Additionally, it was found that the videos effectively illustrated important aspects of experimental chemistry and made students feel as if they were actively participating in the experiments themselves …”
Section: Introductionmentioning
confidence: 99%
“…During that period, it was advised to regularly solicit feedback through low-stakes assignments to assess student learning and improve their courses while they were online . Feedback from students and the utilization of the recorded videos suggested that creating such content was not only valuable at that moment but also for future remote or in-person courses. Additionally, it was found that the videos effectively illustrated important aspects of experimental chemistry and made students feel as if they were actively participating in the experiments themselves …”
Section: Introductionmentioning
confidence: 99%